Bulk (100) scandium nitride crystal growth by sublimation on tungsten single crystal seeds - Al-Atabi, Hayder A.; Khan, Neelam; Nour, Edil; Mondoux, Joseph; Zhang, Yi; Edgar, James H. (My University, 2018)
Scandium nitride single crystals (14–90 μm thick) were grown on a tungsten (100) single crystal substrate by physical vapor transport in the temperature range of 1850 °C–2000 °C and pressure of 15–35 Torr. Epitaxial growth was confirmed using in-plane ϕ scan and out-of-plane x-ray diffraction techniques which revealed that ScN exhibits cube-on-cube growth with a plane relationship ScN (001) ǁ W (001) and normal direction ScN [100] ǁ W [110]. Atomic force microscopy revealed that the surface roughness decreased from 83 nm to 18 nm as the growth temperature was increased. The x-ray diffraction rocking curve (XRC) widths decreased with temperature, indicating that the crystal quality improved as the growth temperature increased. The lowest XRC FWHM was 821 arcsec which is so far the lowest value reported for ScN. Scanning electron microscopy exhibited the formation of macrosteps and cracks on the crystal surface with the latter due to the mismatch of ScN and tungsten coefficients of thermal expansion.
Citation: Al-Atabi, H. A., Khan, N., Nour, E., Mondoux, J., Zhang, Y., & Edgar, J. H. (2018). Bulk (100) scandium nitride crystal growth by sublimation on tungsten single crystal seeds. Applied Physics Letters, 113(12), 122106. https://doi.org/10.1063/1.5051457